2020
DOI: 10.2807/1560-7917.es.2020.25.35.2000011
|View full text |Cite|
|
Sign up to set email alerts
|

Large waterborne Campylobacter outbreak: use of multiple approaches to investigate contamination of the drinking water supply system, Norway, June 2019

Abstract: On 6 June 2019, the Norwegian Institute of Public Health was notified of more than 50 cases of gastroenteritis in Askøy. A reservoir in a water supply system was suspected as the source of the outbreak because of the acute onset and geographical distribution of cases. We investigated the outbreak to confirm the source, extent of the outbreak and effect of control measures. A case was defined as a person in a household served by Water Supply System A (WSS-A) who had gastroenteritis for more than 24 h between 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 35 publications
1
38
1
Order By: Relevance
“…In addition, outbreaks caused by Campylobacter spp. are increasingly being identified and reported on a regular basis, often linked to consumption of untreated drinking water, raw milk or chicken liver paté ( Jakopanec et al., 2008 ; Revez et al., 2014 ; Davis et al., 2016 ; Lahti et al., 2017 ; Kang et al., 2019 ; Hyllestad et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, outbreaks caused by Campylobacter spp. are increasingly being identified and reported on a regular basis, often linked to consumption of untreated drinking water, raw milk or chicken liver paté ( Jakopanec et al., 2008 ; Revez et al., 2014 ; Davis et al., 2016 ; Lahti et al., 2017 ; Kang et al., 2019 ; Hyllestad et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In some of the identi ed articles included in this review, the bene t of combining the surveillance system to geographical supply zones to increase the likelihood of detecting a waterborne outbreak was highlighted. On the other hand, deploying such systems may be challenging, since it will most likely involve two different elds of expertise (health and technical), and the processing of data to inform health decisions must still be accounted for, since local outbreaks are usually short-lived (51).…”
Section: Effectiveness Of Sys Systems In Detecting Waterborne Outbreaksmentioning
confidence: 99%
“…However, none of the excluded studies reported on analysis linked to real or simulated outbreaks. One of the most reported causes of waterborne outbreaks is heavy rainfall, which represents a future increasing risk (53) and implies a greater call for a risk-based approach to surveillance for water supply systems (51). In general, since there will always be a risk of water contamination going undetected, prioritizing long-term preventive measures and risk-based surveillance should not be underestimated despite promising reporting on SyS systems.…”
Section: Effectiveness Of Sys Systems In Detecting Waterborne Outbreaksmentioning
confidence: 99%
“…In Norway, waterborne outbreaks are reported every year, with the second most common microorganism involved being Campylobacter spp. (Hyllestad et al, 2020). The microbiological analysis of water during an outbreak can be challenging, as the contamination is often a short period, and by the time the outbreak is detected, the contamination episode is over (Hänninen et al, 2003;Hyllestad et al, 2020).…”
Section: Introductionmentioning
confidence: 99%